2020
DOI: 10.1093/ecco-jcc/jjaa079
|View full text |Cite
|
Sign up to set email alerts
|

Cell Therapy With Mesenchymal Stem Cells Induces an Innate Immune Memory Response That Attenuates Experimental Colitis in the Long Term

Abstract: Background and Aims Mesenchymal stem cells [MSCs] are used in preclinical and clinical studies for treatment of immune-mediated disorders, thanks to their immunomodulatory properties. Cell therapy with MSCs induces multiple effects in the immune system which ultimately lead to increase in the number of immune cells with regulatory phenotype. In this study, we investigated whether the beneficial effects of MSC therapy are maintained in the long term in a clinically relevant mouse model of coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 57 publications
4
24
0
Order By: Relevance
“…No adverse effects and only a moderate response to the MSC therapy have been observed in all the RA clinical trials conducted so far. Moreover, efficacy observed during 3 years of follow-up [ 42 ] pointed out the long-term effect of MSCs in RA patients in agreement with what has been observed in other immune-mediated diseases [ 18 , 91 ].…”
Section: Clinical Studiessupporting
confidence: 75%
See 1 more Smart Citation
“…No adverse effects and only a moderate response to the MSC therapy have been observed in all the RA clinical trials conducted so far. Moreover, efficacy observed during 3 years of follow-up [ 42 ] pointed out the long-term effect of MSCs in RA patients in agreement with what has been observed in other immune-mediated diseases [ 18 , 91 ].…”
Section: Clinical Studiessupporting
confidence: 75%
“…As a result, MSCs can dampen metabolic reprogramming of different types of immune cells, reduce the proliferation rate of actively dividing cells and inhibit the secretion of inflammatory cytokines. Furthermore, MSCs can promote monocyte differentiation into M2 macrophage [ 15 , 16 , 17 , 18 ]. MSCs can also inhibit monocyte differentiation into dendritic cells and skew them to a tolerogenic profile [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transplantation of BMSCs in a DSS-induced colitis mice model could ameliorate the oxidative stress and restore intestinal mucosal permeability [82]. A single dose of AdSCs in a DSS-induced colitis mice model showed significant reduction in the colitis disease activity index, a concomitant increase in the regulatory/inflammatory macrophage ratio in the colon lamina propria, and a sustained protection against acute inflammation in the long term [83].…”
Section: In Vivo Studies Using Bmscs In the Treatment Of Ucmentioning
confidence: 99%
“…BMSCs have been used by several researchers in the treatment of experimental colitis using various animal models, including mice, rats, and Guinea pigs (Table 4). In these animals, some researchers have used trinitrobenzene sulfonic acid (TNBS) to induce colitis [37,[65][66][67][68], while several studies reported the use of dextran sulfate sodium (DSS) to induce colitis models [47,48,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] and many authors applied acetic acid to induce colitis [1,3,4] (Table 4). The first BMSCs transplantation was conducted in 2006 in a TNBS-induced colitis mice model, revealing the important role of cell therapy in the repair of injured intestinal mucosa, as well as the downregulation of immune function of T cells [65].…”
Section: In Vivo Studies Using Bmscs In the Treatment Of Ucmentioning
confidence: 99%
“…MSCs may also act indirectly, driving the polarization of the functional phenotype of immune cells (31-35). In addition, it has been recently suggested that MSCs could be primed by certain pathogens, which would increase their response to a second stimulus, displaying therefore a trained immunity similarly to innate immune cells (18,(36)(37)(38). Thus, MSCs could be able not only to dampen the inflammatory response but also to enhance bacterial clearance, as has been demonstrated in preclinical models of sepsis, bacterial pneumonia, and acute respiratory distress syndrome (39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 96%